Oil palm shell as an agricultural solid waste in artificial lightweight aggregate concrete - Shafigh, Payam; Salleh, Salmaliza; Ghafari, Hafez; Mahmud, Hilmi (Taylor & Francis, 2018)
The aim of this study was to produce a sustainable construction material by incorporating an agricultural solid waste, namely oil palm shell (OPS), in an artificial lightweight aggregate concrete. For this purpose, in a structural lightweight aggregate concrete made of expanded clay, the lightweight aggregate was substituted with OPS in 0, 25 and 50% by volume. Properties such as compressive strength under different curing conditions, as well as density, splitting tensile and flexural strengths, modulus of elasticity and drying shrinkage of expanded clay–OPS concretes were measured and discussed. The test results showed that partial substitution of expanded clay by OPS increased the density, compressive strength, specific strength (compressive strength to weight ratio), as well as splitting tensile and flexural strengths of lightweight concrete. However, it was observed that the modulus of elasticity decreased by about 4 and 13% in the 25 and 50% substitution levels, respectively. The expanded clay–OPS concretes showed greater drying shrinkage strain compared to expanded clay lightweight concrete. In addition, it was found that the sensitivity of compressive strength of concretes containing OPS to the lack of curing is due to high drying shrinkage and consequently micro-cracks formation in the interfacial transaction zone of the concretes.